Nutrition and Health Education in Rural and Urban Areas of Kansas - Taylor, Melissa N. (My University, 2012)
The overall focus of this experience was to provide efficient nutrition education and health promotion with both rural and urban areas of Kansas. To begin the experience, the student concentrated on health promotion and public health nutrition within the Riley County Research and Extension Office. The second phase of the experience was to provide nutrition education to underprivileged families and adults in Riley County through the Expanded Food and Nutrition Education Program (EFNEP). Classes were facilitated in Manhattan, Kansas and on The Flint Hills Job Corps Campus. During classes, clients were provided with knowledge in many areas including: basic nutrition education, low-cost recipes, and a variety of information related to food, food safety, family nutrition and food resource management. Lastly, to combine coursework, nutrition education experiences, and disease prevention and maintenance, the student established a diabetes education program for JayDoc Free Clinic in Kansas City, Kansas. Every-other Tuesday she volunteered to help educate patients with diabetes during specialty clinic sessions. Instruction was given on insulin use, carbohydrate counting, and prevention and maintenance aspects of this chronic disease to patients and their families. This field experience contains a broad range of public health aspects and provides the chance to work with variety of ages, community members, and healthcare professionals. Direct work with nutrition education provided the student to utilized her core coursework and own experiences to help enable both rural and urban populations to make better lifestyle choices.
Keywords: Nutrition Education; Kansas; Riley County; Research and Extension; JayDoc Free Clinic; Flint Hills Job Corps; Public Health (0573)